Uji Efektivitas Ekstrak Daun Serai Wangi (Cymbopogon nardus L) terhadap Mortalitas Rayap - Ratih Rahhutami (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The lemongrass can increase the number of termites mortality because it contains citronella, geraniol, asetat, and other compounds. Essential oil of lemongrass can be used for soap scents and disinfectant. The objectives of this research were to determine the effectiveness of lemongrass leaves extract as botanical termitisides on mortality of termites and to determine the best rate of lemongrass leaves extract for controlling termites. The research procedur consist of searching the termites to be tested, the preparation of the lemongrass leaves extract, the application of extract to termites, and observation of termite mortality parameter. The experiment was arranged in a completely randomized design with one factor. There are three rates of lemongrass leaves extract : 10 gr/100 ml water (P1), 20 gr/100 ml water (P2), and 30 gr/100 ml water (P3). Each treatments were three replications, and each replications consisted of 15 termites so the total unit of experiments were 135 termites. Data were analized with analysis of variance with α 5 %, If there is a significant treatment effect, the further analysis using Least Significance Different (LSD) test for each of treatments. The result showed that the treatments of lemongrass leaves extract did not significantly affect for all of treatments from 1 hour after application until 3 hour after application for termite mortality parameter and the highest average termite mortality rate can be seen in the 20 gr/l water in 3 hour after application.